1999
DOI: 10.1016/s0954-6111(99)90318-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental asbestos exposure and malignant pleural mesothelioma

Abstract: Asbestos-related benign and malignant pleural diseases are endemic in some rural parts of central Turkey because of environmental exposure to asbestos fibres. We report here epidemiological data on 113 patients with diffuse malignant pleural mesothelioma (DMPM) diagnosed in our clinic in Eskişehir, located in central Turkey. Of the 113 patients, 59 were men and 54 women (male:female ratio = 1). Ninety-seven patients (86%) had non-occupational asbestos exposure; all were living in villages. Their mean age was 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
15

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 12 publications
0
44
0
15
Order By: Relevance
“…39 A meta-analysis examining domestic and neighborhood exposure and risk of pleural mesothelioma reported an RR 5 8.1 (95%CI 5.3-12) for domestic exposure and RR 5 7.0 (95%CI 4.7-11) for neighborhood exposure. 40 This study found that the latency period between exposure to blue asbestos at Wittenoom and diagnosis with malignant mesothelioma in ABA workers was significantly shorter than that in residents and consequently the incidence rate in workers appears to have peaked earlier than that of the residents. We have earlier reported a longer latency period in Wittenoom residents compared with the Wittenoom (male) ABA workers.…”
Section: Discussionmentioning
confidence: 69%
“…39 A meta-analysis examining domestic and neighborhood exposure and risk of pleural mesothelioma reported an RR 5 8.1 (95%CI 5.3-12) for domestic exposure and RR 5 7.0 (95%CI 4.7-11) for neighborhood exposure. 40 This study found that the latency period between exposure to blue asbestos at Wittenoom and diagnosis with malignant mesothelioma in ABA workers was significantly shorter than that in residents and consequently the incidence rate in workers appears to have peaked earlier than that of the residents. We have earlier reported a longer latency period in Wittenoom residents compared with the Wittenoom (male) ABA workers.…”
Section: Discussionmentioning
confidence: 69%
“…MPM etiyolojisinde bilinen iki önemli neden asbest veya erionit lifleriyle temastır. Bu liflerin solunmasıyla hastalık gelişir (8,9). Çev-resel temas ve mesleksel temas olmak üzere iki tür temas mevcuttur.…”
Section: Discussionunclassified
“…Another explanation is that the mean age of the immigrants with relevant exposures (in Belgium, 40¡11 yrs (HMMS inquiry)) is lower than that of the diseased groups in Turkey. For example, pleural calcifications were recorded in 1.7% of the exposed subjects younger than 40 yrs [2], the mean age of those with plaques in Kureysler village is 51 [21] and the mean age of two series of environmental asbestos-related mesothelioma cases in Turkey were 50 [22] and 56 yrs [23], respectively. A steady increase in the number of environmentally-induced, asbestosrelated diseases could thus be foreseen for the next 20 yrs when the Turkish immigrant population is aging.…”
Section: Discussionmentioning
confidence: 99%